Alcohol consumption and the body's biological clock - Spanagel, Rainer; Rosenwasser, Alan M.; Schumann, Gunter; Sarkar, Dipak K. (Alcoholism, 2006)
This review summarizes new findings on the bidirectional interactions between alcohol and the clock genes, underlying the generation of circadian rhythmicity. At the behavioral level, both adult and perinatal ethanol treatments alter the free-running period and light response of the circadian clock in rodents; genetic ethanol preference in alcohol-preferring rat lines is also associated with alterations in circadian pacemaker function. At the neuronal level, it has been shown that ethanol consumption alters the circadian expression patterns of period (per) genes in various brain regions, including the suprachiasmatic nucleus. Notably, circadian functions of β-endorphin-containing neurons that participate in the control of alcohol reinforcement become disturbed after chronic alcohol intake. In turn, per2 gene activity regulates alcohol intake through its effects on the glutamatergic system through glutamate reuptake mechanisms and thereby may affect a variety of physiological processes that are governed by our internal clock. In summary, a new pathologic chain has been identified that contributes to the negative health consequences of chronic alcohol intake. Thus, chronic alcohol intake alters the expression of per genes, and, as a consequence, a variety of neurochemical and neuroendocrine functions become disturbed. Further steps in this pathologic chain are alterations in physiological and immune functions that are under circadian control, and, as a final consequence, addictive behavior might be triggered or sustained by this cascade.